1983
DOI: 10.1104/pp.71.2.291
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of [15N]Nitrate and [15N]Nitrite in Leaves of Five Plant Species under Light and Dark Conditions

Abstract: Light dependency of nitrate and nitrite assimilation to reduced-N in leaves remains a controversial issue in the literature. With the objective of resoling this controversy, the lght requirement for nitrate and nitrite assimilation was investigated in several plant species. Dark and light assimilation of I'5Nlnitrate and 1"Nlnitrite to a ium and am_io-N was determined with leaves of wheat, corn, soybean, sunflower, and tobacco. In dark aerobic conditions, assimilation of I1Nlnitrate as a percentage of the lght… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 17 publications
2
35
0
Order By: Relevance
“…shown for various lines of wild-type tobacco that nitrate as well as nitrite reduction can take place in the dark in leaves, although at a reduced rate (Reed et al, 1983;Lejay et al, 1997). The values obtained in this work are very similar to those obtained previously for the wild-type and Del lines using detached leaves (Lejay et al, 1997).…”
supporting
confidence: 79%
“…shown for various lines of wild-type tobacco that nitrate as well as nitrite reduction can take place in the dark in leaves, although at a reduced rate (Reed et al, 1983;Lejay et al, 1997). The values obtained in this work are very similar to those obtained previously for the wild-type and Del lines using detached leaves (Lejay et al, 1997).…”
supporting
confidence: 79%
“…Nitrogen assimilation is also suppressed by a reduction in carbohydrate status (Fritz et al 2006), and therefore by the duration of the dark period. Nevertheless, nitrate reduction often continues in the dark, albeit often at reduced rates (9-76% of diurnal rates in a range of species [Reed et al 1983];~50% [Aslam et al 1979] or 88% [Bloom et al 1989] in Hordeum vulgare L.). In species that perform little or no nitrate reduction in leaves, amino acid synthesis in leaves does not, in principle, require light.…”
Section: The Role Of Variation In Anabolic Demandsmentioning
confidence: 99%
“…Plants can assimilate NO3-during both the light and dark portions of the photoperiod, although rates of assimilation may differ. In experiments using '"NO3-and excised leaves or leaf disks, it has been amply demonstrated that N03 reduction can occur in darkness (8,11,24,32), and the rate of reduction is associated with availability ofcarbohydrate (2, 15). Nevertheless, it was found consistently that reduction rates were lower in darkness.…”
Section: Introductionmentioning
confidence: 99%